Public spendings: an analysis about the Fiscal Responsibility Law and Federal Constitution application at COREDE Alto Jacuí - Berlt, Cristiano; Bender Filho, Reisoli; Tristão, Pâmela Amado (Revista de Administração da UFSM, 2017)
Planning and public spending control are one of the most important parts of the new regime in public administration. In this context, the objective of this work is to analyze the limits established by the Fiscal Responsibility Law (LRF) and Federal Constitution at COREDE Alto Jacuí from 2005 to 2008. The analyses have indicated that the LRF is not being applied in all the cities in this study due to the fact that the ordinary and integral legal limits established have not been applied. Furthermore, it could be observed that the value spent with salaries has grown continually during the period analyzed, mainly in cities with less population and economically smaller. Although the limits invested in education and health are according to the percentage in law, the majority of the cities in this study have shown contrasting results, and many cities with similar structure have had different results considering the areas studied, leading to the conclusion that heterogeneity in terms of size (populations and taxes collected) may be not a determinant observed factor in the legal limits.